The effect of mental health interventions on psychological distress for informal caregivers of people with mental illness: A systematic review and meta-analysis - Hansen, Nanja Holland; Bjerrekær, Lasse; Pallesen, Karen Johanne; Juul, Lise; Fjorback, Lone Overby (Frontiers in Psychiatry, 2022)
Informal caregivers of people with a mental illness are at increased risk for developing depression, anxiety and stress, and preventive interventions are needed. The review was reported in Prospero, Id: CRD42018094454. PsycINFO, PubMed, and Scopus databases were searched June 2019, and the Cochrane Risk of Bias and Jadad scale score was used to assess study quality. Inclusion criteria were: RCTs of informal caregiver interventions regardless of care-receiver mental illness and intervention modality. Interventions should be compared to a waitlist, treatment as usual or active control, taught in real-time by a mental health professional, and include an outcome measure on psychological distress, published in a peer reviewed journal article in English. RCTs were excluded if the intervention was given in dyads (caregiver + care-receiver), limited to the provision of respite care, when the patient sample included a mix of both physical and psychological illness, were unpublished, not peer reviewed, a study protocol, or a dissertation. 2148 studies were identified, of those forty-four RCT studies met inclusion criteria and thirty-one studies had sufficient data to conduct a meta-analysis including subgroup analysis (N=1899). The systematic review showed that thirty-one out of forty-four RCTs had effect of the intervention on decreasing psychological distress. Results of the meta-analysis, which included informal caregiver interventions, compared to waitlist, treatment as usual, or active control, regardless of care-receiver mental illness, or intervention modality showed a small effect 0.34 (95% CI -0.55 to -0.13. Heterogeneity of the included studies was high (I2 78). Subgroup analysis including manualized interventions lasting at least eight-weeks and subgroup analysis that included an active control showed a small effect and low heterogeneity. Lack of active control and long-term follow-up are limitations in most studies. Evidence supports that several interventions improve mental health in caregivers. Manualized interventions, ≥ 8 weeks with active participation are effective. Future RCTs should improve methodology and research should investigate, which intervention modality is most effective for what kind of caregiver. Future research should clearly specify what the included interventions components are, use longer follow-up times and conduct mediational analyses to better understand what creates the effect of an intervention.